A study on factors that influence demand of housing loan in Malaysia / Mohammad Aizal Anuar - Anuar, Mohammad Aizal (2011)
This project paper attempts to identify the important factors that contribute significantly to demand of housing loan in Malaysia. During the Asian Financial crisis in 1997 and late 1998, the demand of housing seems be affected by the crisis. Due to unstable economic condition at that time, housing loan is less demand and Malaysian people do not affordable to buy a house. The empirical evidence from many literatures witnessed that some of independent variables (interest rate, statutory reserve requirement, inflation rate and gross domestic product) have significant effect to the dependant variable (demand of housing loan). So, the primarily focus of this paper is, attempt to study on the relationship between independent variables (interest rate, statutory reserve requirement, inflation rate and gross domestic product) affects on the dependent variable demand of housing loan in Malaysia. This is important because this area of study has not been greatly researched in Malaysia. With that, interest rate, statutory reserve requirement, inflation rate and gross domestic product will be put as independent variables and demand of housing loan will be as the dependent variable. The aims of this present study are twofold: firstly to identify the relationship between inflation and interest rate, statutory reserve requirement, inflation rate and gross domestic product variables and secondly, to identify the most influenced factor that will affect demand of housing loan in Malaysia. A multiple linear regression model is employed to find the relationship between independent and dependent variable. All the data used, are in quarterly basis range from 1997 to 2010. The results indicate that only interest rate statutory reserve requirement and gross domestic product show a positive significant relationship towards the demand of housing loan in Malaysia. Meanwhile the inflation rate shows an insignificant negative relationship towards the demand of housing loan in Malaysia. Furthermore, the results by other researchers found that inflation rate is significant towards the demand of housing loan. This is maybe because inflation rate does not suitable to put together with others independent variables in this study. Hence, this study found that interest rate is the most influenced variable towards the demand of housing loan in Malaysia